2012
DOI: 10.1111/j.1464-410x.2012.11369.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy techniques can accurately distinguish benign and malignant renal tumours

Abstract: What's known on the subject? and What does the study add?• There is little known about optical spectroscopy techniques ability to evaluate renal tumours.• This study shows for the first time the ability of Raman and optical reflectance spectroscopy to distinguish benign and malignant renal tumours in an ex vivo environment. We plan to develop this optical assistance in the operating room in the near future. Objective• To evaluate the ability of Raman spectroscopy (RS) and optical reflectance spectroscopy (ORS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
(53 reference statements)
0
23
0
Order By: Relevance
“…They reported that RA-MS was able to discriminate with high accuracy (specificity and sensitivity of >80%) between (i) normal and tumor tissues, (ii) benign and malign tumors, (iii) low-grade and high-grade tumors, and 4) clear cell carcinoma, papillary tumors, and chromophobe tumors. Couapel et al 177 confirmed these results by distinguishing between benign and malignant renal tumors using RA-MS in combination with supervised multivariate processing.…”
Section: Vibrational Imaging: a Powerful Emerging Toolfor Scientists mentioning
confidence: 83%
“…They reported that RA-MS was able to discriminate with high accuracy (specificity and sensitivity of >80%) between (i) normal and tumor tissues, (ii) benign and malign tumors, (iii) low-grade and high-grade tumors, and 4) clear cell carcinoma, papillary tumors, and chromophobe tumors. Couapel et al 177 confirmed these results by distinguishing between benign and malignant renal tumors using RA-MS in combination with supervised multivariate processing.…”
Section: Vibrational Imaging: a Powerful Emerging Toolfor Scientists mentioning
confidence: 83%
“…Compared to previous studies [9, 10], we first provided characteristic Raman spectrum for each type of renal tumor. These spectra could potentially serve as chemical “fingerprints” and be used for pre-operative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…And it needs no sample pre-treatment or external labeling, and requires only a few seconds. Previous publications have presented the use of RS to detect the whole mass of renal tumor [9, 10], but no study on Raman's investigation of biopsy specimen was ever reported. In this context, we mimicked pre-operative RMB by collecting biopsy specimen from surgical removed kidney to determine whether RS is able to distinguish malignant and benign renal tumors, and serve as a complementary diagnostic tool in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy for distinguishing between histological subtypes was 88-90 % overall and 89-95 % for small renal masses. Accuracy for distinguishing between chromophobe RCC and benign histology was 98-100 % [ 15 ]. To date, these fi ndings have not been investigated in vivo and technology that would enable this is pending.…”
Section: Light Refl Ectance Spectroscopy In Kidneysmentioning
confidence: 92%
“…Recently, Couapel et al investigated the ability of light refl ectance spectroscopy and Raman spectroscopy to differentiate benign from malignant renal tissue as well as to differentiate between histological subtypes of RCC [ 15 ]. Spectra were collected prospectively in a cohort of 60 patients who underwent radical or partial nephrectomy for suspicion of cancer.…”
Section: Light Refl Ectance Spectroscopy In Kidneysmentioning
confidence: 99%